Hubungan Paparan Debu Terhirup Terhadap Gangguan Fungsi Paru Pada Pekerja Bongkar Muat Di Pelabuhan Manado Sulawesi Utara Tahun 2017 - Ombuh, Richard Victor; Nurjazuli, Nurjazuli; Raharjo, Mursid (HIGIENE: Jurnal Kesehatan Lingkungan, 2017)
Upper respiratory tract infection has been one of top ten illness the last three years. In 2014 (28.579 cases), in 2015 (39.110 cases) and in August 2016 (27.068 cases). In community health service of Manado Port area, upper respiratory tract infection is on the top list. The high numbers of upper respiratory tract infection in the living area of loading and unloading workers and the high numbers of fatigue factor caused by heavy activities of the workers is assumed to be allegedly related with the inhaled dust exposure to lung function problems of loading and unloading workers in Manado Port. This research was conducted to analyze the relation of inhaled dust exposure and lung function problem of loading and unloading workers in Manado Port. The research was observational with analytical approach and cross sectional design, with 60 samples of respondents. It consisted of 9 variables and the data was collected by interview, observation and measurement. Bivariate analysis result proved that the risk factor of lung problems are use of mask (p=0,195; PR=0,648(95% CI=0,533 – 0,789). Smoking habit (p=0,786; PR=0,788(95% CI=0,361 – 1,719). Working period (p=0,143; PR=1,959(95% CI=0,896 – 4,283). Working duration (p=0,838; PR=0,831(95% CI=0,390 – 1,771) With potential variables affecting lung function impairment of loading and unloading workers is use of mask (p=0,195) and period of work (p=0,143). There’s no significant correlation between use of mask, smoking habit, period of work, working duration, inhaled dust exposure and lung function disorder. Keywords : inhaled dust exposure, lung function disorder, Manado Port